2010
DOI: 10.2527/jas.2009-2127
|View full text |Cite
|
Sign up to set email alerts
|

Additive genetic relationships between scrotal circumference, heifer pregnancy, and stayability in Nellore cattle

Abstract: Scrotal circumference data from 47,605 Nellore young bulls, measured at around 18 mo of age (SC18), were analyzed simultaneously with 27,924 heifer pregnancy (HP) and 80,831 stayability (STAY) records to estimate their additive genetic relationships. Additionally, the possibility that economically relevant traits measured directly in females could replace SC18 as a selection criterion was verified. Heifer pregnancy was defined as the observation that a heifer conceived and remained pregnant, which was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 16 publications
3
39
3
5
Order By: Relevance
“…The genetic correlation between SC and HP (0.30 6 0.03) was higher than the estimates reported by Eler et al 2004 and2006 (0.11 to 0.27) and similar to that reported by Van Melis et al (2010;0.29). The mean posterior genetic correlation between SC and STAY (0.17 6 0.04) differed from that reported by Silva et al (2006;0.27) and Evans et al (1999; estimate close to 0).…”
Section: Genetic Correlationscontrasting
confidence: 50%
See 2 more Smart Citations
“…The genetic correlation between SC and HP (0.30 6 0.03) was higher than the estimates reported by Eler et al 2004 and2006 (0.11 to 0.27) and similar to that reported by Van Melis et al (2010;0.29). The mean posterior genetic correlation between SC and STAY (0.17 6 0.04) differed from that reported by Silva et al (2006;0.27) and Evans et al (1999; estimate close to 0).…”
Section: Genetic Correlationscontrasting
confidence: 50%
“…Nieto et al (2007) reported an estimate of 0.07 for Canchim animals (5/8 Charolais : 3/8 Nellore). Van Melis et al (2010) found a heritability of 0.10 6 0.01 for Nellore cattle belonging to the same herd as the animals studied in our experiment. The genetic gain obtained by selection for STAY is therefore expected to be small.…”
Section: Heritability Estimatesmentioning
confidence: 69%
See 1 more Smart Citation
“…Under such conditions, AFC may be negatively correlated with longevity, given that the younger heifers (born at the end of the birth season) have less probability to become pregnant at the end of the breeding season. However, Van Melis et al (2010) studied data from farms at which heifers were exposed to breeding at an early age (,14 months of age) and found a positive correlation (0.64) between heifer pregnancy and longevity. The longest interval between calvings occurs between the first and second calving (Werth et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Pereira et al (2008) reported the estimates of the annual genetic trend of breeding values of 0.98 kg for yearling weight and 0.27 kg for 18-month weight, respectively, for a Caracu beef herd. The available data for scrotal circumference indicated an increase in the trend, which has a positive implication for improved fertility, as scrotal circumference was found to have close relationships with spermatozoa quality and quantity in bulls and age at puberty in bulls' daughters (Kealey et al, 2006;Van Melis et al, 2010). The five breeds included in this study are not currently at risk of losing genetic diversity.…”
mentioning
confidence: 97%